Political cycles of media repression - Günther G. Schulze; Nikita Zakharov (University of Freiburg, Department of International Economic Policy (iep), 2025)
In this paper, we unveil targeted repression against journalists as an elaborate strategy used by modern autocrats to mitigate the risk of mass protests during autocratic elections-a common threat to their rule. Repression is deployed to discipline the media before elections to secure favorable media coverage of the incumbent, thereby discourage public dissent. In contrast, the reigns are loosened during off-election periods to allow the media's credibility to be rebuilt. This dynamic creates distinct electoral cycles of media repression in autocracies. Our empirical study establishes these cycles using a unique granular dataset on the harassment of journalists in Putin's Russia and the predetermined, staggered timing of local elections. We then demonstrate the disciplinary effects on reporting about incumbents using a novel media coverage index. Finally, employing survey data, we show that media repression is extremely effective when it comes to dwarfing the threat of anti-government protests.
Keywords: D72; H10; P43; 330; Autocracy; elections; media repression; political cycles; protest